2006
DOI: 10.1016/j.icesjms.2005.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria in the gut of juvenile cod Gadus morhua fed live feed enriched with four different commercial diets

Abstract: Atlantic cod, Gadus morhua L., larvae were fed rotifers, Brachionus plicatilis and Artemia franciscana enriched on four different commercial media, using the manufacturers' protocols. Pooled samples of 20 cod larvae were homogenized, diluted, and plated out on Petri dishes. The number of colony-forming units per larva was estimated, and the dominant strains subsequently sampled for sequencing of 16S rDNA. Bacteria showing high sequence similarity to a pathogen characteristic of cod and other fish species, List… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…Some certain strains of these bacteria possess the virulence factors necessary to induce disease (Cahill, 1990). Vibrio species have previously been detected in gut of a wide variety of fishes, such as halibut larvae (Verner-Jeffreys et al, 2003;Jensen et al, 2004), hybrid tilapia (Oreochromis niloticus) (Al-Harbi and Uddin, 2004), Atlantic cod (Gadus morhua) (Korsnes et al, 2006;Ringø et al, 2006), Atlantic salmon (Salmo salar) (Hovda et al, 2007) and so on, and the importance of the genera Vibrio in aquaculture have been discussed (Thompson et al, 2004;Austin, 2006). Shewanella putrefaciens is a potential pathogen of fish, and has been isolated from the intestine of rainbow trout (Oncorhynchus mykiss) (Huber et al, 2004;Koziñska and Pêkala, 2004;Pond et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some certain strains of these bacteria possess the virulence factors necessary to induce disease (Cahill, 1990). Vibrio species have previously been detected in gut of a wide variety of fishes, such as halibut larvae (Verner-Jeffreys et al, 2003;Jensen et al, 2004), hybrid tilapia (Oreochromis niloticus) (Al-Harbi and Uddin, 2004), Atlantic cod (Gadus morhua) (Korsnes et al, 2006;Ringø et al, 2006), Atlantic salmon (Salmo salar) (Hovda et al, 2007) and so on, and the importance of the genera Vibrio in aquaculture have been discussed (Thompson et al, 2004;Austin, 2006). Shewanella putrefaciens is a potential pathogen of fish, and has been isolated from the intestine of rainbow trout (Oncorhynchus mykiss) (Huber et al, 2004;Koziñska and Pêkala, 2004;Pond et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In intensive aquaculture, cod larvae are offered rotifers, usually Brachionus plicatilis, and brine shrimp, mostly Artemia franciscana, as live feed (Svåsand et al 2004, Reitan 2005. Recently, Korsnes et al (2006) demonstrated the presence of bacteria with high sequence similarity to Vibrio anguillarum in rotifer cultures and the gut of cod larvae fed rotifers. Both rotifers and Artemia sp.…”
Section: Discussionmentioning
confidence: 99%
“…High larval densities and suboptimal rearing conditions may provide a good environment for opportunistic bacterial pathogens to flourish (Vadstein et al 2004), and high rates of mortality are still common. Commercial enrichment diets for rotifers may enhance the growth of pathogens including Vibrio anguillarum (Korsnes et al 2006). Adult cod are frequently subject to classical vibriosis caused by V. anguillarum (reviewed by Samuelsen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During first feeding, yolk-sac larvae in general are subject to a massive inflow of bacteria from the live feed organisms Brachionus plicatilis and Artemia spp., and suspected pathogens, like Listonella anguillarum, may be accumulated in the live feed (Korsnes et al 2006). The mucosal surfaces of fish serve as a substrate for bacterial adhesion (Hansen & Olafsen 1989).…”
Section: Bacteria Associated With Early Life Stagesmentioning
confidence: 99%